High frequency ultrasonography: reliable tool to measure skin fibrosis in SSC? A systematic literature review and additional pilot study. (25th May 2021) - Vanhaecke, Amber; Cutolo, Maurizio; Heeman, Lise; Vilela, Veronica; Deschepper, Ellen; Melsens, Karin; Smith, Vanessa
Abstract: Objectives: To investigate the reliability of high frequency ultrasound (HFUS) in measuring skin fibrosis in SSc. Methods: First, a systematic review (according to PRISMA) was conducted to identify studies that documented HFUS' reliability in SSc as a primary outcome. Then, in an additional pilot study, the inter- and intra-rater reliability of two investigators performing HFUS for dermal thickness (DT) measurements in a standardized manner across all 17 areas of the modified Rodnan Skin Score was evaluated in a group of 59 SSc patients and descriptively in 44 healthy controls (HC). As an external validation, DT measurements by HFUS were performed in a separate group of 30 SSc patients by the same first and another third investigator. Results: The systematic review retained few (4/1719 unique records) small-scale studies, with mixed study populations (combining SSc and HC). The reported data herein are suggestive of the inter-/intra-rater reliability of HFUS (intra-class correlation coefficient [ICCs] ranging 0.65–0.94/0.55–0.96, respectively). Additionally, in our pilot study, inter-/intra-rater reliability was good-to-excellent in both SSc groups and HC (ICCs ranging 0.70–0.97/0.70–0.98 and 0.65–0.95/0.63–0.96, respectively). Conclusion: The identified small-scale studies were not only combining data from SSc and HC, they were also heterogeneous in terms of technical aspects (probes and frequency), image acquisition methods ([number of] areas assessed) and definitions used for skin thickness, which prevents drawing unequivocal conclusions. Despite these limitations, our standardized pilot study corroborated the findings in literature, paving the way for the applicability of HFUS as a reliable (complementary) tool to quantify skin fibrosis in SSc.